IDENTIFIKASI SENYAWA ANTIBAKTERI PADA DAUN KECAPI (Sandoricum koetjape (Burm.f.) - Dira Swantara, I M.; Ciawi, Yenni (Jurnal Kimia (Journal of Chemistry); Vol. 3, No. 2 Juli 2009, 2012)
Identification of antibacterial compound for Micrococcus luteus dan Eschericia coli bacteri have been conducted to kecapi leaf extract (Sandoricum koetjape (Burm.f.)). Extraction of that compounds was carried out by maseration methods using 70% etanol. Separation of the fraction by liquid-liquid partition (n-hexane, ethyl acetate and chloroform) and two step column chromatographic method using silicagel as stationary phase and ethyl acetate – chloroform (3:7;2,5:7,5; dan 2:8) as first eluent and ethyl acetate – chloroform (2:8; 1,5:8,5; dan 1:9) as second eluent. The active fraction (2.1 and 2.3 fraction) were identified by gas chromatography-mass spectroscopy (GCMS). The 2.1 fraction contain 3 compound which are heksil n-valerate (C11H22O2); 2,3-dihidrobenzofurane (C8H8O); and 2,6-dimetoxy fenol (C8H10O3). The 2.3 fraction contain 2 compound which are ester dioctilehexadioat (C22H42O4) with M+ = 370 and basic peak equal to 129 and 3,5-di-tert-buthyl-4-hydroxy-toluene (C15H24O).
Keywords: isolation, identification, Sandoricum koetjape (Burm.f.), antibacterial